Analisis Dampak Program Keluarga Harapan terhadap Penurunan Kemiskinan di Kecamatan Kesamben Kabupaten Jombang - Agus Raikhani; Muchtar Muchtar; Elok Faikotul Himmah (Journal of Public Power, 2024)
This article aims to analyze the influence of the Family Hope Program social assistance on poverty reduction among beneficiary families in Kesamben Subdistrict, Jombang Regency. The study was developed from quantitative research involving 97 respondents representing a population of 2,813 beneficiary families. The independent variables include the utilization of assistance in the health, education, and economic sectors, while the dependent variable is poverty reduction. Data were collected through questionnaires, observation, documentation, and interviews, and then analyzed using descriptive statistics, classical assumption tests, partial tests, simultaneous tests, multiple linear regression, and coefficient of determination. The findings show that all instruments were valid and reliable, the residuals were normally distributed, and there were no symptoms of multicollinearity, heteroscedasticity, or autocorrelation. Partially, the health sector had a significant effect with a significance value of 0.000, the education sector had a significant effect with a significance value of 0.004, and the economic sector had a significant effect with a significance value of 0.018. Simultaneously, the three variables had a significant effect with an F value of 97.043 and a significance value of 0.000. The R Square value of 0.758 indicates that 75.8 percent of the variation in poverty reduction can be explained by the three variables. These findings confirm that conditional social assistance functions not only as a consumption buffer, but also as an instrument for behavioral change, improved access to basic services, and strengthening the economic capacity of poor households.